The role of grit and classroom enjoyment in EFL learners' willingness to communicate - Lee, Ju Seong (Journal of multilingual and multicultural development, 2022)
This interdisciplinary study investigates whether, and to what extent, grit (consisting of perseverance of effort and consistency of interests) and classroom enjoyment are linked with EFL learners' willingness to communicate in a second language (L2 WTC), the final psychological step before actual English communication. To this end, three groups of Korean EFL learners (N = 647) from five schools, who at the time of the study had no overseas experience, were surveyed: middle school (n = 137), high school (n = 323), and university students (n = 187). Results of hierarchical regression analyses show that grit (perseverance of effort) and classroom enjoyment are predictors of all cohorts' L2 WTC, while grit (consistency of interests) is not predictive of L2 WTC among all participants. These results suggest that L2 teachers, who instruct in a relatively monolingual and monocultural EFL classroom, can boost learners' L2 WTC by encouraging continuous efforts to initiate English communication. Moreover, by creating a positive classroom environment, EFL teachers can increase learners' level of L2 WTC and potentially boost their English communicative competence. Theoretically, these findings support an emerging view of the application of positive psychology in L2 learning and teaching.